Hak Negara untuk Mengontrol Sumber Daya Alam di Indonesia: Review Putusan Mahkamah Konstitusi - Ritonga, Rifandy; Isharyanto, Isharyanto; Rudy, Rudy; Vivi Pusita Sari A.P, Aulia Oktarizka (As-Siyasi: Journal of Constitutional Law, 2021)
This study aims to look at the interpretation and impact of the decisions of the Constitutional Court relating to the review of laws relating to the State's Right to Control in the management of natural resources. This research is a normative legal research using secondary data which includes primary, secondary and tertiary legal materials. The approach used is a statutory approach. The results of the study found that on the one hand it is a guideline for understanding and interpreting Article 33 of the 1945 Constitution which has been amended. On the other hand, from several Judicial Review made by the Constitutional Court, there are legal uncertainties, one of which is the Oil and Gas Law and the Electricity Law. In addition, the lack of uniformity in understanding natural resources in every decision of the Constitutional Court also causes differences in understanding in interpreting Natural Resources to be included in the law.